Same Fate, Different Choices: Decolonization in Vietnam and Indonesia, 1945–1960s - Pham van Thuy (Lembaran Sejarah, 2017)
The purpose of this study is to sketch out the similarities and differences in the process of decolonization in Indonesia and Vietnam during the period from the 1930s to the early 1960s, with special attention to the political and economic aspects. Both countries shared similarities in that they were the first countries to declare independence in Southeast Asia from the Japanese and that they were highly revolutionized during the occupation. Both countries had the most violent and complete colonial break in comparison to other Southeast Asian countries. Yet, there were some major differences within the process of decolonization, especially during the final phase. Indonesia opted for a diplomatic peace process and eventually obtained a transfer of sovereignty from the Netherlands in late 1949, while Vietnam continued military struggle against the French until 1954. This resulted in highly different patterns of the economic decolonization, such as the process of nationalization, the government policies concerning foreign investments and the extent of state control over the economy. French businesses in Vietnam were ruined in the North following the withdrawal of French army in 1954-1955. Their remaining assets in South Vietnam were shortly also taken over by the Diem government. Meanwhile, the Dutch continued to dominate the Indonesian economy after the transfer of sovereignty. It was not until the late 1950s that Dutch firms were seized and finally nationalized by the Indonesian government.